Exploring the interplay between anxiety and academic procrastination: An institution-based cross-sectional study from Pakistan - Alishba Hameed; Hamna Noor; Muhammad Abdullah Ali; Zaryab Bacha; Umama Alam; Sidra Irfan (Industrial Psychiatry Journal)
Background: Procrastination, the unnecessary delay of tasks, is common among college students, especially in academic settings. Academic procrastination often leads to last-minute rushes and increased anxiety. The relationship between procrastination and anxiety is intricate, complicating the determination of which triggers the other. Aim: To examine how anxiety and procrastination interact among medical students, particularly focusing on their reciprocal influence. Materials and Methods: This descriptive cross-sectional study included 311 MBBS students, recruited through simple convenient sampling. Procrastination was assessed with the Irrational Procrastination Scale (IPS) and anxiety with the Generalized Anxiety Disorder 7-item (GAD-7) scale. Data analysis was conducted using SPSS version 27, with Chi-square tests, Pearson correlation, and linear regression. Statistical significance was set at P < 0.05. Results: Pearson correlation showed a significant, weak positive correlation between anxiety and procrastination (r = 0.346, P < .001). Subcategories of the IPS correlated with anxiety from negligible to high. Chi-square analysis found a significant association of anxiety with procrastination (P < 0.001) and gender (P = 0.038), but no significant link of anxiety or procrastination with the year of study was observed. Linear regression revealed that anxiety significantly predicted procrastination (B = 0.354, P < 0.05) and vice versa (B = 0.339, P < 0.05), explaining 12% of the variance. Conclusion: The study found a weak yet significant positive correlation between anxiety and procrastination, indicating that the relationship might be bidirectional. However, the cross-sectional design and reliance on self-reported data highlight the need for further longitudinal research to better understand these dynamics.